A study on crude palm oil, rubber and cocoa prices towards inflation, Kuala Lumpur composite index and bond index in Malaysia / Nor Faeiqah Mustaffa - Mustaffa, Nor Faeiqah (Faculty of Business and Management, 2006)
This study is aimed to analyze the potential benefits of considering crude palm oil, rubber and cocoa as an alternative investment in a portfolio. This study is conducted to analyze the risk and return of the main commodities that are traded in Malaysia. It is also to study the correlation of its returns with stock and bond as well as its correlation with inflation. This study is also done to know whether the commodities such as crude palm oil, rubber and cocoa could be consider as a part of a portfolio and provide diversification towards the portfolio. From the study, the rubber does provide the highest return other than CPO and Cocoa. Furthermore, cocoa represents the higher risk and higher return assets as compared to CPO that has the highest risk in lower return. The results indicate that the commodities do have weak positive relationships towards KLCI. The negative relationship towards bond index only occurs for CPO and Rubber. Meanwhile the commodity such as cocoa has a weak positive relationship against bond. The study also found that KLCI and Bond index have negative relationships towards inflation whereby the commodities especially CPO and Rubber have positive relationships with inflation. However, Cocoa has no linear relationship against inflation. From the findings, the commodities are better to be hold by an investor with other types of investment asset, due to its higher risk. By using the Sharpe's Index, the commodities tend to stand in the highest ranking as compared to stock and bond